2008
DOI: 10.1063/1.2916588
|View full text |Cite
|
Sign up to set email alerts
|

A new magic titanium-doped gold cluster and orientation dependent cluster-cluster interaction

Abstract: The stability and structures of titanium-doped gold clusters AunTi (n=2–16) are studied by the relativistic all-electron density-functional calculations. The most stable structures for AunTi clusters with n=2–7 are found to be planar. A structural transition of AunTi clusters from two-dimensional to three-dimensional geometry occurs at n=8, while the AunTi (n=12–16) prefer a gold cage structure with Ti atom locating at the center. Binding energy and second-order energy differences indicate that the Au14Ti has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…Walter and Häkkinen [29] studied theoretically the endohedral M@Au 16 [M = Si and Al] clusters by using density functional theory and Born–Oppenheimer molecular dynamics, concluding that Si@Au 16 is a magic species with 20 delocalized electrons. Chen et al studied the titanium-doped small gold clusters Au n Ti (n = 2 – 16) [30], and Zorriasatein et al investigated the electronic and structural properties of the copper-doped gold clusters, Au n Cu − (n = 12 – 18) [31]. Doping of the gold cage Au 16 − with Si, Ge, and Sn has also appeared in literature [32].…”
Section: Introductionmentioning
confidence: 99%
“…Walter and Häkkinen [29] studied theoretically the endohedral M@Au 16 [M = Si and Al] clusters by using density functional theory and Born–Oppenheimer molecular dynamics, concluding that Si@Au 16 is a magic species with 20 delocalized electrons. Chen et al studied the titanium-doped small gold clusters Au n Ti (n = 2 – 16) [30], and Zorriasatein et al investigated the electronic and structural properties of the copper-doped gold clusters, Au n Cu − (n = 12 – 18) [31]. Doping of the gold cage Au 16 − with Si, Ge, and Sn has also appeared in literature [32].…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that both of the two clusters display a relative closure of electron shell. Therefore, the larger gap of the (CoRh) 2 and (CoRh) 4 clusters should be mainly originate from their relative closure of electron shell [35].…”
Section: Binding Energy and Energy Gapmentioning
confidence: 98%
“…Fig. 4 shows the prole of HOMO-LUMO gap 50,54 for the W nanocluster with different sizes. It can be found that almost all gaps of W n (n ¼ 2-16) were larger than 0.15 eV.…”
Section: Small W N (N ¼ 2-16) Nanocluster and Dft Calculationmentioning
confidence: 99%